2003
DOI: 10.1111/j.1365-2621.2003.tb05715.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Moisture in Maillard Browning Reaction Rate in Intermediate Moisture Foods: Comparing Solvent Phase and Matrix Properties

Abstract: In intermediate-moisture foods, a mechanism describing how moisture affects chemical reaction rate is unknown. Previously, research showed glycol addition to model systems allowed high rates of nonenzymatic browning below the monolayer moisture value and an a w of 0.2. These works were replicated, focusing on a mechanism of either plasticization or reactant dissolution. T g curves showed plasticization increased with added glycerol and sorbitol. The maximum rate of nonenzymatic browning with glycerol occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…Darkening as a result of reduced a w was the only effect discernible by the eye. Several researchers reported enzymatic or non-enzymatic browning in meat, due to the reactivity of fruit or glycerol with protein (Sherwin and Labuza, 2003). However, the addition of sorbitol, kiwi and pineapple did not show a significant difference in L * compared to the control.…”
Section: Color Analysismentioning
confidence: 82%
“…Darkening as a result of reduced a w was the only effect discernible by the eye. Several researchers reported enzymatic or non-enzymatic browning in meat, due to the reactivity of fruit or glycerol with protein (Sherwin and Labuza, 2003). However, the addition of sorbitol, kiwi and pineapple did not show a significant difference in L * compared to the control.…”
Section: Color Analysismentioning
confidence: 82%
“…The findings of this study agree with Park and Park (2007) noted that meat color values (L*, a* and b*) were higher in the air-blast dried beef jerky than in the hot airdried samples and the drying methods showed the great- est effect on the redness (a*). Sherwin and Labuza (2003) showed that discoloration of jerky products could be affected by temperature. It is assumed that hot air and shade-dried jerky might have a discoloration due to the high temperature in hot air-dried and drying for a long time in shade-dried.…”
Section: Color Measurementsmentioning
confidence: 99%
“…In this study, as the addition of RBF increased, the proportion of meat to the proportion of total weight decreased, this may be caused the percent of metmyoglobin decreased. In general, myoglobin denaturation is affected by grinding and mixing (Govindarajan et al, 1997), processing temperature (Sherwin and Labuza, 2003), the addition of salt (Huffman et al, 1981) and lipid oxidation (Faustman and Cassens, 1990). …”
Section: A -Dmentioning
confidence: 99%